Spatial Transformation Agriculture to Industry and Social Change in the Peasant Community of Noborejo Subdistrict - Intan Feranita; Daru Purnomo; Suryo Sakti Hadiwijoyo (Universitas Medan Area, 2023)
The spatial transformation in the Noborejo Subdistrict caused the change from an agricultural area to an industrial one. This transformation impacts society, from assets, and access to social changes in the community. Assets consist of land ownership and income of the farming community, while access is related to access to work for the people of the Noborejo Village community. Spatial transformation is also inseparable from social change, patterns of behavior, and social interaction of people when they experience changes from agrarian to industrial. This study aims to identify the transformation of the agricultural to industrial space in the Noborejo Subdistrict and analyze the effect of the transformation of the agricultural to industrial space on assets, access, and social change in the Noborejo Subdistrict, Argomulyo District, Salatiga City. The problem is focused on spatial transformation and its impact on society to find out what changes and influences have occurred after the change in space. To approach this problem, theoretical references from Marxists are used. The data are collected through interviews, observation, and documentation, then analyzed qualitatively. This study concludes that the transformation of the agrarian to industrial space that occurred in Noborejo occurred after Noberejo changed from a village to a sub-district and joined the City of Salatiga, this change from an agricultural area to industry greatly impacted the assets, access, and social changes of the Noborejo community.